Effects of scarification and storage on vigor expression of Albizia lebbeck (L.) Benth seeds - Navarro, Marlen; Febles, Gustavo; Torres, Verena (Cuban Journal of Agricultural Science, 2016)
An experiment was developed to estimate vigor of A. lebbeck seeds, related to the effect of scarification treatments (sulfuric acid, hot water, 24 h soak, cover cutting, puncture and control) and storage time (0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 and 12 months after initiated the storage, mais) with vigor expression. According to the methodology, the analyzed variables were: days before the beginning of emergence (E), percentage of final emergence during test period (Emer), peak day (PD), peak emergence (PE), germination value (GV), germination energy (Ener) and emergence rate (ER). These variables were evaluated at the nursery. A general assessment of results shows the negative effects of acid and hot water methods on vigor expression of albizia seeds. It may be concluded that pre-sowing treatments, applied through dry and wet scarification, showed cut efficiency of cover and soak, respectively, as promoting methods of germination, emergence and efficiency of vigor. Except acid and hot water treatments, the rest of the treatments showed the best expression of variables related to vigor at 3 mais. Key words: germination, emergence, greenhouse